Genistein Inhibits the Pathogenesis of Aeromonas hydrophila by Disrupting Quorum Sensing Mediated Biofilm Formation and Aerolysin Production - Dong, Jing; Zhang, Defu; Li, Jianrong; Liu, Yongtao; Zhou, Shun; Yang, Yibin; Xu, Ning; Yang, Qiuhong; Ai, Xiaohui (Frontiers in Pharmacology, 2021)
Aeromonas hydrophila is an opportunistic pathogen that is responsible for a variety of infectious diseases both in human and animals, particular aquatic animals. Moreover, the pathogen has become a foodborne pathogen by transmitting from seafood to human. The abuse of antibiotics in aquaculture results in the emergence of antibiotic resistance and treatment failure. Therefore, novel approaches are urgently needed for managing resistant A. hydrophila associated infections. Aerolysin, an essential virulence factor of pathogenic A. hydrophila strain, has been identified as target developing novel drugs against pathogenesis of A. hydrophila. In the present study, genistein, without anti-A. hydrophila activity was identified that could decrease the production of aerolysin and biofilm formation at a dose-dependent manner. Transcription of aerolysin encoding gene aerA and quorum sensing related genes ahyI and ahyR was significantly down-regulated when co-cultured with genistein. Cell viability studies demonstrated that genistein could significantly improve aerolysin mediated A549 cell injury. Furthermore, genistein could provide a remarkable protection to channel catfish infected with A. hydrophila. These findings indicate that targeting quorum sensing and virulence can be a useful approach developing drugs against A. hydrophila infections in aquaculture. Moreover, genistein can be chosen as a promising candidate in developing drugs against A. hydrophila.